A field study on pile response to blast-induced ground motion - Jayasinghe, Laddu Bhagya (2020)
A series of field tests using controlled blasting was conducted at a location in the North Western part of Singapore to assess the behaviour of pile foundations subjected to ground excitation. The field tests involved three piles with different pile head fixity conditions. The piles were instrumented with strain gauges to evaluate the bending moments and axial force along the piles. For the fixed-head piles, the maximum bending moment occurred at the pile head level. For free-head pile exhibited higher bending moments close to the mid-height of the pile and zero bending moment at the pile head due to the absence of restraints at the top. For all cases, the axial force was maximum at the pile head.